Ventilatory threshold and maximal oxygen uptake in present triathletes - Hue, O.; Le Gallais, D.; Chollet, D.; Prefaut, Ch. (Canadian Journal of Applied Physiology, 2000)
The aim of this study was to determine the physiological profile of young triathletes who began triathlon competition as their first sport. Twenty-nine male competitive triathletes (23 regionally and nationally ranked triathletes and 6 elite, internationally ranked triathletes) performed two tests, one on a cycle ergometer (CE VáO2max) and one on a treadmill (TM VáO2max). Results showed (a) no difference between CE VáO2max and TM VáO2max in the triathletes (69.1 ± 7.2 vs. 70.2 ± 6.2 mL á kgÐ1 á minÐ1, respectively), (b) values of CE VáO2max and TM VáO2max in elite triathletes (75.9 ± 5.2 and 78.5 ± 3.6 mL á kgÐ1 á minÐ1, respectively) that were comparable to those reported in elite single-sport athletes in these specialities, and (c) although the ventilatory threshold (Thvent) was similar in CE and TM, TM Thvent was consistently lower for triathletes than TM Thvent usually reported for runners.